Carbonic anhydrase IV and XIV knockout mice: Roles of the respective carbonic anhydrases in buffering the extracellular space in brain - Shah, Gul N. (National Academy of Sciences, 2005)
Previous studies have implicated extracellular carbonic anhydrases (CAs) in buffering the alkaline pH shifts that accompany neuronal activity in the rat and mouse hippocampus. CAs IV and XIV both have been proposed to mediate this extracellular buffering. To examine the relative importance of these two isozymes in this and other physiological functions attributed to extracellular CAs, we produced CA IV and CA XIV knockout (KO) mice by targeted mutagenesis and the doubly deficient CA IV/XIV KO mice by intercrossing the individual null mice. Although CA IV and CA XIV null mice both are viable, the CA IV nulls are produced in smaller numbers than predicted, indicating either fetal or postnatal losses, which preferentially affect females. CA IV/XIV double KO mice are also produced in fewer numbers than predicted and are smaller than WT mice, and many females die prematurely before and after weaning. Electrophysiological studies on hippocampal slices on these KO mice showed that either CA can mediate buffering after synaptic transmission in hippocampal slices in the absence of the other, but that eliminating both is nearly as effective as the CA inhibitor, benzolamide, in blocking the buffering seen in the WT mice. Thus, both CA IV and CA XIV contribute to extracellular buffering in the central nervous system, although CA IV appears to be more important in the hippocampus. These individual and double KO mice should be valuable tools in clarifying the relative contributions of each CA to other physiological functions where extracellular CAs have been implicated.